Synthesis and in vitro evaluation of potential antichagasic dipeptide prodrugs of primaquine - Chung, M. C.; Goncalves, M. F.; Colli, W.; Ferreira, E. I.; Miranda, MTM (Amer Pharmaceutical Assn, 1997)
American trypanosomiasis (Chagas' disease) is an endemic parasitic disease afflicting more than 20 million people in Latin America. Currently, therapy is unsatisfactory and only two drugs are available. Primaquine, an antimalarial drug, has trypanocidal activity. Dipeptide derivatives of primaquine, Phe-Arg-PQ, Lys-Arg-PQ, and Phe-Ala-PQ, were synthesized. The choice of the peptides was based on the primary specificity of cruzipain, the major cysteine proteinase from T. cruzi. The prodrugs obtained were tested on the LLC-MK2 cell culture infected with trypomastigotes forms of T. cruzi Phe-Arg-PQ, Lys-Arg-PQ, and Phe-Ala-PQ were active in all stages.